Methanol poisoning: a diagnostic challenge in high anion gap metabolic acidosis - Lai, Yin Ye; Lim, Chee Hoe; C. Thambiah, Subashini; Samsudin, Intan Nureslyna (Universiti Putra Malaysia, 2023)
A 47-year-old gentleman was admitted with decreased responsiveness and vomiting. Clinically, he had altered mental status, pupils sluggish to light and laboured breathing. Thoracoabdominal examination and computed tomography of the brain were normal. Preliminary laboratory testing revealed high anion gap metabolic acidosis (HAGMA). Blood acetaminophen and urine paraquat were negative. Serum salicylate was not measured however respiratory alkalosis typical of salicylate intoxication was absent. Normoketonaemia and normoglycaemia rendered diabetic ketoacidosis improbable, whilst uraemia was ruled out as renal profile was only moderately impaired. Raised plasma lactate was inadequate to account for the magnitude of HAGMA, leading to a suspicion of ethylene glycol or methanol poisoning. Despite early treatment with intravenous ethanol, the patient died at day three of admission. Blood methanol concentration which was obtained on admission and reported three days later by the referral toxicology lab affirmed the diagnosis of methanol poisoning. Methanol poisoning can be challenging in situations where patient is obtunded and methanol analysis not widely available.